Event-based cybersecurity risk assessment - Wan Mohamad, Wan Azlena; Abdul Molok, Nurul Nuha; Abd Rahim, Noor Hayani (KICT Publishing, 2024)
In today’s digital age, organisations’ dependence on technology for operational efficiency, improved service delivery, and client interaction has grown considerably. This increasing reliance has, however, also amplified vulnerability to cyber risks, underscoring the urgent need for effective cybersecurity risk management within organisations. Cybersecurity risk management involves the identification, assessment, and mitigation of threats to safeguard individuals, organizations, and nations from cyber risks. At the heart of this process is the cybersecurity risk assessment, a crucial activity focused on understanding and mitigating potential cyber threats. Two main approaches are commonly employed in risk assessment: the event-based approach and the asset-based approach. Here, an "event" denotes any occurrence or shift in circumstances that might affect security. This study investigates the event-based risk assessment by assessing potential cyber-attacks or events that could compromise the confidentiality, integrity, and availability of digital data, thereby posing significant cybersecurity risks to organizations. Academic research has often focused on asset-based methods, potentially weakening strategies against new and emerging cyber threats. Many academic findings are tailored to specific application systems or sectors, which might not adequately address the unique risks and necessary controls pertinent to different sectors. Moreover, there is a noticeable disconnect between academic approaches and established cybersecurity guidelines that align with international standards, such as those from the National Institute of Standards and Technology (NIST) and the International Organization for Standardization (ISO). To bridge these gaps, this study examines an event-based cybersecurity risk assessment for organisations. Utilizing a qualitative research approach, interviews will be conducted with risk assessment officers who have served in the organisations for over 10 years and have experience in cybersecurity risk assessment within them. Through thematic analysis of the qualitative data, this study aims to examine an event-based cybersecurity risk assessment, contributing to the strengthening of the cybersecurity framework within organisations.